EFFECT OF ADDING Piminella Anisum and Nigella SativaSEEDS ON QUALITY PROPERTIES OF LABORATORYSHORTENED CAKE - Al- Ani, Ibtihal (Iraqi Journal of Science, 2024)
The aim of this study was to investigate the effect of addition of Pimpinellaanisum (PA) and Nigella sativa (NS) seeds in different percentages on the physical,sensory and microbial properties of the shortened cake. The results revealed thatcake size of treatments 3 (0+3%PA and NS) and 6 (2+1% PA and NS) weresignificantly lager than that of treatmant (1) control. The results of sensoryevaluation showed that treatments 2 (1.5+1.5% PA and NS), 3, 4 (3+0%PA andNS), 5 (1+2%PA and NS) and 6 were not significantly higher than the control in theoverall acceptance. Treatments 4 and 6 gained higher score of overall acceptancethan treatments 2, 3 and 5. Other treatments, however, did not show significant